Lo scavo di Palazzo Legnani Pizzardi a Bologna: l’epigrafia anforica - Curina, Renata; Mongardi, Manuela (Rei Cretariae Romanae Fautorum Acta, 2022)
Between 2006 and 2008 the Soprintendenza Archeologia, belle arti e paesaggio per la città metropolitana di Bologna e per le province di MO, RE, FE carried out an excavation in the courtyard of Palazzo Legnani Pizzardi, which in Roman times was located in the first southern suburb of Bononia. As for the Roman period, a big hollow has been found, which probably belonged to the original defence system of the colony; afterwards, perhaps since the Augustan age, the hollow was filled with both ceramics and materials derived from the demolition of upmarket buildings. In particular, a considerable amount of amphorae has been found, 25 of them bearing stamps: one on Lamboglia 2, eight on Dressel 2–4, nine on Dressel 6A and seven on Dressel 6B amphorae. All these containers were produced in the Adriatic area, mainly in its northern part, and are mainly dated from the Augustan age to the Early Imperial age. In addition to that, a Dressel 7–11 amphora has been found, which bears a poorly preserved painted inscription mentioning the mur(ia) hisp(ana).